Answer:
59
Explanation:
The first step here is to rewrite -8z -8x + 5a + 5c - 8y + 5b as
-8x - 8y - 8z + 5a + 5b + 5c.
This is the same as -8(x + y + z) + 5(a + b + c).
Subbing -8 for (x + y + z) and -1 for (a + b + c), we get -8(-8) - 5, or 59.
a + b + C = -1
x + y + z = -8
We want 5a so multiply the first equation by 5
5(a + b + c) = -1*5
5a+5b+5c = -5
We want -8x so multiply the second equation by -8
-8(x + y + z) = -8*-8
-8x-8y-8x = 64
Add these equations together
---------------------------
-8x -8y-8x+5a+5b+5c = 59
Rearrange the order
-8z -8x + 5a + 5c - 8y + 5b = 59
5.1m questions
6.7m answers